Gut Microbiota and SCFAs Play Key Roles in QingFei Yin Recipe Anti-Streptococcal Pneumonia Effects - Sun, Xiaozhou; Wang, Dandan; Wei, Lina; Ding, Lizhong; Guo, Yinan; Wang, Zhongtian; Kong, Yibu; Yang, Jingjing; Sun, Liwei; Sun, Liping (Frontiers in Cellular and Infection Microbiology, 2021)
Emerging evidence has revealed the presence in animals of a bidirectional regulatory “lung-gut axis” that provides resistance to respiratory infections. Clues to the existence of this system stem from observations that respiratory infections are often accompanied by gastrointestinal symptoms, whereby intestinal microbiota appear to play pivotal roles in combating pathogenic infections. Importantly, short-chain fatty acids (SCFAs) produced by the gut microbiota appear to serve as the biological link between host immune defenses and gut flora. Streptococcus pneumoniae (S.pn), the main cause of lower respiratory tract infections, is involved in more than 1.189 million deaths per year. QingFei Yin (QFY) is known for its excellent therapeutic efficacy in combating bacterial lung infections. In this study, effects of S.pn infection on gut homeostasis were assessed using 16S RNA-based microbiota community profiling analysis. In addition, potential mechanisms underlying QFY recipe beneficial therapeutic effects against bacterial pneumonia were explored using S.pn-infected gut microbiota-depleted mice. Results of data analysis indicated that QFY treatment alleviated lung infection-associated pathogenic processes, while also promoting repair of disordered gut flora and counteracting S.pn infection-associated decreases in levels of SCFAs, particularly of acetate and butyrate. Mechanistically, QFY treatment suppressed inflammatory lung injury through inhibition of the host NF-κB-NLRP3 pathway. These results inspired us to identify precise QFY targets and mechanisms underlying QFY anti-inflammatory effects. In addition, we conducted an in-depth evaluation of QFY as a potential treatment for bacterial pneumonia.